Sustained Transmission of Pertussis in Vaccinated, 1–5-Year-Old Children in a Preschool, Florida, USA - James Matthias; P. Scott Pritchard; Stacey W. Martin; Cristina Dusek; Erika Cathey; Rebecca D’Alessio; Marjorie Kirsch (Emerging Infectious Diseases, 2016)
In September 2013, local county health officials in Tallahassee, Florida, USA, were notified of a laboratory-confirmed pertussis case in a 1-year-old preschool attendee. During a 5-month period, 26 (22%) students 1–5 years of age, 2 staff from the same preschool, and 11 family members met the national case definition for pertussis. Four persons during this outbreak were hospitalized for clinical management of pertussis symptoms. Only 5 students, including 2 students with pertussis, had not received the complete series of vaccinations for pertussis. Attack rates in 1 classroom for all students who received the complete series of vaccinations for pertussis approached 50%. This outbreak raises concerns about vaccine effectiveness in this preschool age group and reinforces the idea that recent pertussis vaccination should not dissuade physicians from diagnosing, testing, or treating persons with compatible illness for pertussis.